RAZVOJ PRERAĐENIH MESNIH PROIZVODA SA MALO MASTI I MALO SOLI - Mourtzinos, Ioannis (Journal on Processing and Energy in Agriculture, 2020)
There is a growing demand for the development of healthier meat products with reduced fat and salt. The present study was carried out to develop low fat – low salt processed meat products like sausages. Products were formulated with different fat contents (10% - 20%) and levels of NaCl substitution with KCl (0% - 50%). Physicochemical characteristics and textural attributes were assessed instrumentally, while sensory attributes were determined using Quantitative Descriptive Analysis and Principal Component Analysis. The instrumental analysis showed significant (p